STUDY OF ALTERNATIVE FUELS AND EFFECTS OF COMPRESSION RATIO ON THERMAL EFFICIENCY AND ENGINE POWER - Sarjito, Sarjito (Media Mesin: Majalah Teknik Mesin, 2007)
This paper was a case study during the sabatical program at Kingston University London in February 2007. It has been studied by team of motorsport automotive department Kingston University London and it has been elaborated as a final project on Master Program. This study takes into account some of the issues surrounding the debate about alcohol fuels in Motorsport and the wider automotive sector and is primarily concerned to add data where there seems to be little existing research since Motorsport is a secretive business. Motorsport plays an important part in the automotive industry and is a sport enjoyed worldwide. Racing practice is regarded as using the best available resources and technology as it requires optimal performance. The racing arena gives engineers the opportunity to test valuable technological solutions to prove their merits. Therefore, racing is the natural starting point for introducing new technological solutions to the public and could lead to the wholesale conversion to renewable fuels to meet our automotive energy needs. Alcohol has unique properties that make superior in many ways to ordinary gasoline. The higher knock resistance allows for higher compression ratios to be utilized resulting in higher power outputs and thermal efficiency. The efficient use of energy is of growing concern in all spheres of life and the automotive sector needs to be front runner in these efforts.